Hypomorphic conditional deletion of E11/Podoplanin reveals a role in osteocyte dendrite elongation. Issue 11 (14th June 2017) - Staines, Katherine A.; Javaheri, Behzad; Hohenstein, Peter; Fleming, Robert; Ikpegbu, Ekele; Unger, Erin; Hopkinson, Mark; Buttle, David J.; Pitsillides, Andrew A.; Farquharson, Colin
Abstract : The transmembrane glycoprotein E11/Podoplanin (Pdpn) has been implicated in the initial stages of osteocyte differentiation. However, its precise function and regulatory mechanisms are still unknown. Due to the known embryonic lethality induced by global Pdpn deletion, we have herein explored the effect of bone‐specific Pdpn knockdown on osteocyte form and function in the post‐natal mouse. Extensive skeletal phenotyping of male and female 6‐week‐old Oc ‐cre; Pdpn flox/flox (cKO) mice and their Pdpn flox/flox controls (fl/fl) has revealed that Pdpn deletion significantly compromises tibial cortical bone microarchitecture in both sexes, albeit to different extents ( p  < 0.05). Consistent with this, we observed an increase in stiffness in female cKO mice in comparison to fl/fl mice ( p  < 0.01). Moreover, analysis of the osteocyte phenotype by phalloidin staining revealed a significant decrease in the dendrite volume ( p  < 0.001) and length ( p  < 0.001) in cKO mice in which deletion of Pdpn also modifies the bone anabolic loading response ( p  < 0.05) in comparison to age‐matched fl/fl mice. Together, these data confirm a regulatory role for Pdpn in osteocyte dendrite formation and as such, in the control of osteocyte function. As the osteocyte dendritic network is known to play vital roles in regulating bone modeling/remodeling, this highlights an essential role for Pdpn in bone homeostasis. Abstract : E11/Pdpn has been implicated in the initial stages of osteocyte differentiation; however, its precise function and regulatory mechanisms are still unknown. Using a bone‐specific Pdpn knockout mouse, we have confirmed a regulatory role for Pdpn in osteocyte dendrite formation and as such, in the control of osteocyte function.